2011
DOI: 10.1002/ar.21438
|View full text |Cite
|
Sign up to set email alerts
|

Development and Expression of Amyloid‐β Peptide 42 in Retinal Ganglion Cells in Rats

Abstract: The previous studies have shown that Amyloid-b peptide (Ab) was mainly found in neurons of neurodegenerative diseases, such as Alzheimer's disease (AD) and glaucoma and little is known about its expression in normal nerve cells. The aim of the present study was to investigate the expression of amyloid-b peptide 42 (Ab-42) in retinal ganglion cells of the postnatal rats. Rats were divided into seven experimental groups: 3, 6, 13, 15, 25, 60, and 90 days postnatal groups. Rats from 15 and 25 days postnatal group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Although APP/Aβ immunoreactivity was previously reported in whole retinal mounts, in RGC, the inner nuclear layer and on photoreceptors (Dasari et al., 2011, Dutescu et al., 2009, Guo et al., 2007, Hoh et al., 2010, Kipfer-Kauer et al., 2010, Koronyo-Hamaoui et al., 2011, Wang et al., 2011), we wanted to establish whether a predetermined amount of physiological Aβ 1-42 was realistically capable of localising to the living retina. To assess if this was possible, ∼2 μl of oligomeric of Aβ 1-42 (625 nM) was subretinally injected into C57BL/6 wildtype mice to recapitulate the elevated Aβ burden reported in aged and AMD retinas (Ratnayaka et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although APP/Aβ immunoreactivity was previously reported in whole retinal mounts, in RGC, the inner nuclear layer and on photoreceptors (Dasari et al., 2011, Dutescu et al., 2009, Guo et al., 2007, Hoh et al., 2010, Kipfer-Kauer et al., 2010, Koronyo-Hamaoui et al., 2011, Wang et al., 2011), we wanted to establish whether a predetermined amount of physiological Aβ 1-42 was realistically capable of localising to the living retina. To assess if this was possible, ∼2 μl of oligomeric of Aβ 1-42 (625 nM) was subretinally injected into C57BL/6 wildtype mice to recapitulate the elevated Aβ burden reported in aged and AMD retinas (Ratnayaka et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings by other groups revealed that Aβ also activated the complement system to bring about a state of chronic inflammation in subretinal tissues (Catchpole et al., 2013, Koyama et al., 2008, Wang et al., 2008, Wang et al., 2012b, Yoshida et al., 2005). However, retinal neurons are also immunopositive for APP/Aβ (Dasari et al., 2011, Dutescu et al., 2009, Guo et al., 2007, Hoh et al., 2010, Kipfer-Kauer et al., 2010, Koronyo-Hamaoui et al., 2011, Wang et al., 2011), suggesting that Aβ activity is not exclusive to the RPE. Therefore, to fully understand how Aβ could impair the senescent eye, it was important to study whether the neuroretina is also affected by this neurotoxic group of peptides.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations